2013
DOI: 10.1371/journal.pone.0071978
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 in Pancreatic Ductal Adenocarcinoma Tumor-Associated Fibroblasts Promotes Metastasis

Abstract: IntroductionPancreatic ductal adenocarcinoma (PDAC) is projected to rise to the second leading cause of U.S. cancer-related deaths by 2020. Novel therapeutic targets are desperately needed. MicroRNAs (miRs) are small noncoding RNAs that function by suppressing gene expression and are dysregulated in cancer. miR-21 is overexpressed in PDAC tumor cells (TC) and is associated with decreased survival, chemoresistance and invasion. Dysregulation of miR regulatory networks in PDAC tumor-associated fibroblasts (TAFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 46 publications
(54 reference statements)
5
119
1
Order By: Relevance
“…They confirmed transfer of miR‐21 from primary CAFs to ovarian cancer cells by co‐culturing CAFs transfected with labeled miR‐21 with ovarian cancer cells (Au Yeung et al ., 2016). In addition, miR‐21 was frequently upregulated in CAFs from both human pancreatic ductal adenocarcinoma samples and primary cell cultures, and higher expression of miR‐21 was significantly correlated with decreased overall survival in pancreatic ductal adenocarcinoma patients (Donahue et al ., 2014; Kadera et al ., 2013). In esophageal squamous cell carcinoma, miR‐21 expression in tumor tissues was found to be primarily localized in the stroma adjacent to the cancer cells (Nouraee et al ., 2013).…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…They confirmed transfer of miR‐21 from primary CAFs to ovarian cancer cells by co‐culturing CAFs transfected with labeled miR‐21 with ovarian cancer cells (Au Yeung et al ., 2016). In addition, miR‐21 was frequently upregulated in CAFs from both human pancreatic ductal adenocarcinoma samples and primary cell cultures, and higher expression of miR‐21 was significantly correlated with decreased overall survival in pancreatic ductal adenocarcinoma patients (Donahue et al ., 2014; Kadera et al ., 2013). In esophageal squamous cell carcinoma, miR‐21 expression in tumor tissues was found to be primarily localized in the stroma adjacent to the cancer cells (Nouraee et al ., 2013).…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…5,17 Overexpression of miR-21 is associated with the progression, metastasis and poor prognosis of many types of tumours via its regulation of the phosphatase and tensin homologue (PTEN), the tissue inhibitor of metalloproteinase 3 and PDCD4 genes. [6][7][8] A study of 127 primary melanoma tissues demonstrated that levels of miR-21 were significantly increased compared with benign naevi. 18 Increased expression of miR-21 was also demonstrated in 86 primary cutaneous melanomas and expression levels were correlated with Breslow thickness and advanced clinical stage.…”
Section: Discussionmentioning
confidence: 99%
“…[15] In addition, miR-21 was frequently upregulated in CAFs in various entities. [16,17] Moreover, expression of this miR in stellate cells derived from normal pancreas was substantially lower when compared to PSCs or CAF cells. [4] Specific upregulation of miR-409-3p and miR-409-5p was found in prostate cancer stromal tissue specimens [18], whereas miR-15 and miR-16 were downregulated in fibroblasts surrounding prostate tumors [19].…”
Section: Clinical Relevance Of Mir In Cafmentioning
confidence: 99%
“…These genome-wide screenings provided potentially deregulated miRNAs in CAFs from different entities (upregulated: miR-221-5p, miR-31-3p, miR-221-3p; and reduced: miR-205, miR-200b, miR-200c, miR-141, miR-101, miR-342-3p, let-7g, miR-26b). (Table 1) Prognostic impact of altered miR expression in CAFs in clinical cohorts has been observed for patients with breast cancer (miR-26b) [11], gastric cancer (miR-106b [22], miR-143 [23], miR-145 [24], miR-200b [14]), esophageal carcinoma (miR-21 [16], miR-27a/b [25]) and pancreatic adenocarcinoma (miR-21 [16]). Furthermore, miR-21 expression in CAFs was elevated in colorectal cancer specimens compared to fibroblasts in colonic polyps [26] and it was associated with decreased overall survival in pancreatic cancer patients who received 5-FU, but not gemcitabine.…”
Section: Clinical Relevance Of Mir In Cafmentioning
confidence: 99%